DIAGNOSTIC PARAMETERS OF THE MODEL OBJECT - KUTINA, MARYNA; KOVALOV, ARTEM (Herald of Khmelnytskyi National University. Technical sciences, 2023)
A method of analysis of the diagnostic model is proposed to determine the parameters used for the properties of the model and to evaluate its elements, namely, the determination of the area of influence of the parameters of the graph, the section of the model of the independent part of the stacking of the top of the graph. The vertices of the graph model are evaluated using an integral indicator, and the edges of the graph are evaluated by the amount of information they convey. In recent years, the load on distribution networks, which supply mainly domestic consumers, has increased significantly, and the consumption of electrical energy by the industrial sector has significantly decreased.
Keywords: diagnostic parameters; models; electrical equipment